THE ABILITY TO EXPLORE TEXT DRAMA IN ENGLISH WITH THE CIRC (COOPERATIVE, INTEGRATED, READING AND COMPOSITION) - Mona Fitri Gurusinga; Meta Rosaulina; Saiful Batubara; Afrilius Simanjuntak (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
This study aims to determine the effects of the use of the Cooperative Integrated Reading and Composition (CIRC) Model on the Students' Ability to analyze the content and language of drama reading at SMA Bina Guna Tanah Jawa Balimbing, Kec. Tanah Jawa, Simalungun Regency in 2020/2021. This research was conducted based on  5 classes with a total population of class , of 160 students. From the population, a sample of 32 students was assigned to one class, selected by cluster sampling, namely class XI IPA 1. The data collection technique was used to measure students’ learning outcomes in the form of assignment questions carried out on the pretest and posttest. The data analysis technique used is normality test using F test, homogeneity test and hypothesis testing using t test. The hypothesis in this study was tested by t-test at a significant level = 0.05. From the calculation of the data it was seen that  t-count t-table (10.3722000). Thus the null hypothesis is that Ho is rejected and Ha is accepted. From the results, it can be concluded that the Cooperative Integrated Reading and Composition (CIRC) Model can improve students’ learning outcomes in analyzing the content and language of drama.